SDM dan Modal Sosial dalam Jaringan Bisnis Komunitas Tarekat di Yogyakarta - M. Supraja (Jurnal Ilmu Sosial dan Ilmu Politik, 2010)
This paper generally highlights the relation between economic and religion, specifically what so-called tarekat. Terminologically, tarekat is defined as the way to find the bridge between trancendental aspects (God) and social aspects. Moreover, the author in this paper also explores the broaden perspectives of tarekat itself. Hence, this paper also tries to explain how tarekat gives significant contribution to develop business of its member by activating theis social capital. Social capital of tarekat has given many advantages, especially when there is little or no support from the government in the forms of aids or policies.